SURGICAL APPROACH IN PATIENTS WITH CATASTROPHIC ABDOMEN: CHALLENGES AND INNOVATIONS - Moura Carias, Pedro; Almeida do Nascimento, Evelyn; Almeida Cabral dos Santos Lugão, Matheus; Pedro Rocha Morozini, João; Henrique Braga, Pedro; Leite Bicalho, Rebeca; Garcia Lima, Carolina; Luiza Cerutti Dutra, Ana; Fernanda Santos, Evelyn; Bandeira Lima, Júlia; Costa Pignaton, Maycon; Stein de Siqueira Varejão, Amanda; et al. (Health and Society, 2024)
Catastrophic abdomen, characterized by severe abdominal dysfunction due to trauma, infection or surgical complications, represents one of the greatest challenges in emergency surgery. The condition requires rapid and effective interventions, given the high mortality rate and the significant impact on the quality of life of surviving patients. The aim of this study is to analyze the challenges faced in the surgical approach to catastrophic abdomen and to explore the technical and technological innovations that have contributed to improving clinical outcomes. This is a literature review with a qualitative approach, using the PubMed, Scopus and Web of Science databases. To ensure accuracy in the selection of studies, health descriptors (DeCS/MeSH) such as “Intra-abdominal Infections,” “Sepsis Management,” and “Abdominal Compartment Syndrome” were used. The search was carried out using Boolean operators, covering the period from 2019 to 2021, according to the time frame of the selected references. The surgical management of catastrophic abdomen requires a multidisciplinary approach, with an initial focus on damage control to stabilize the patient. Techniques such as laparostomy with progressive traction closure and the use of negative pressure therapy have proven effective in managing abdominal compartment syndrome, a common complication. In addition, advances in hemodynamic monitoring and the use of biomaterials for abdominal wall reconstruction have allowed for greater safety in definitive surgeries. Among the main challenges are the control of resistant intra-abdominal infections, the hemodynamic fragility of patients and the need for prolonged intensive care in the post-operative period. Therefore, the surgical approach to the catastrophic abdomen has evolved significantly with the development of modern techniques and advanced technologies. However, the complexity of the clinical picture requires specialized training and well-established protocols to optimize outcomes. The integration of innovative strategies and a focus on individualized care are fundamental to reducing the morbidity and mortality associated with this critical condition.